2019
DOI: 10.1186/s42834-019-0009-4
|View full text |Cite
|
Sign up to set email alerts
|

A system for monitoring water quality in a large aquatic area using wireless sensor network technology

Abstract: In this paper, a low cost, real-time water quality monitoring system which can be applied in remote rivers, lakes, coastal areas and other water bodies is presented. The main hardware of the system consists of off-the-shelf electrochemical sensors, a microcontroller, a wireless communication system and the customized buoy. It detects water temperature, dissolved oxygen and pH in a pre-programmed time interval. The developed prototype disseminates the gathered information in graphical and tabular formats throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 31 publications
(33 reference statements)
2
72
0
1
Order By: Relevance
“…The comparison of proposed systems to similar systems published by other researchers on some aspects is summarised as follows. Compared to other published research results in [7], [8], [10], and [12], the proposed system has shown work as expected when implemented in the actual field since it has been tested on actual river with data acquisition and base station were separated in the distance of 100 m while most other similar systems were tested in laboratory scale. The use of the blynk cloud application for storing and visualizing the measured data enabled the data could be accessed anywhere so that it supported mobility compared to when the measured data were stored in a dedicated computer.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The comparison of proposed systems to similar systems published by other researchers on some aspects is summarised as follows. Compared to other published research results in [7], [8], [10], and [12], the proposed system has shown work as expected when implemented in the actual field since it has been tested on actual river with data acquisition and base station were separated in the distance of 100 m while most other similar systems were tested in laboratory scale. The use of the blynk cloud application for storing and visualizing the measured data enabled the data could be accessed anywhere so that it supported mobility compared to when the measured data were stored in a dedicated computer.…”
Section: Discussionmentioning
confidence: 68%
“…This scenario is less practicable if the proposed system would be implemented in a remote area in a long period of time since it will need frequent activities to check the condition of batteries and possible replacement with the new one. Energy harvesting for example such as proposed in [20] or by using photovoltaic (PV) such as proposed in [8] could be considered to be applied. Moreover, the warning message when any water parameter above its standard such as using buzzer [21], Short Message Services (SMS) of Global System Mobile (GSM) networks [13] or Telegram application [19] would be useful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is one of the most important natural resources on the earth. 1 There are alkali metal ions such as Na + and K + and alkaline earth metal ions such as Mg 2+ and Ca 2+ in the water, which are essential nutrient elements for the living organism. However, some heavy metal ions such as Pb 2+ , Hg 2+ , and Cd 2+ are considered as the typical water pollutants 2 because they are nonbiodegradable and can accumulate in organisms through the food chain.…”
Section: Introductionmentioning
confidence: 99%
“…These vehicles may not be capable of traveling the long range required for a WARM application. Moreover, static SNs powered by a solar panel [39], wireless power transmission [40], and network-connected sensors using ZigBee [41] need a large number of BSs for wider coverage. Satellite-based wireless data transmission is used in [42] for remote locations, but it is cost-intensive when using a large number of SNs.…”
Section: Introductionmentioning
confidence: 99%